Gestão de lições aprendidas em projetos de tecnologia da informação – avaliação de um modelo suportado por tecnologias colaborativas 2.0 - Winter, Roberto Antonio (2016)
Organizational learning process is part of the quest for competitiveness and it is also present on the project’s results, summing up together with several organization projects in order to make up its result. The learned lessons support managers in their projects with the successful and unsuccessful experiences through the registry stored and provided in a centralized and organized way. The learned lessons registry in any project stage helps the project members to meditate about the process, achievements, stimulating the sharing of tacit and explicit knowledge created. On this process of storing and retrieving learned lessons, the web’s 2.0 collaborative tools are present, and in this context the wiki platform is one of the most cited when storing and retrieving learned lessons. Add up the fact that there are no process on the most used references (PMBOK-PMI and ICB-IPMA) to these factors and it is identified a gap on the studies. This scenario motivates the quest for a model that helps the learned lessons management in Information Technology projects and Information Systems. This dissertation aims to evaluate a learned lesson management model on IT/IS project utilizing web 2.0 tools. This model supports the management of learned lessons: gathering, verification, dissemination and reusing. This study has an explanatory and prescriptive approach using an abductive, inductive and deductive method. The Design Science Research is the research’s approach. This study looks for contributing towards the project’s practice and its results and creating academic knowledge with the accuracy that the study requires in its method. The Target 2.0 was instantiated in the implementation phase of an IT project, demonstrating that the model achieved its expected results, solving while searching the company's problem with the GLA. The result emerged evidence of the sociomaterial relations, the quality of relations between people and the model, under present social theory. The research contributes to the GLA practice in projects, helps with project managers in GLA, besides contributing to the Administration allowing expand the use of the organization's knowledge management model. The research contributes to the theory and use of GLA model in the implementation phase of an IT project, in a small business, with improvements in GLA.